THE CORRELATION BETWEEN THE EIGHT GRADE STUDENTS’ READING MOTIVATION AND READING COMPREHENSION ACHIEVEMENT - Eka Agustina (Sriwijaya University Learning and Education International Conference, 2018)
The main objectives of this research was to find out whether or not there was a statically significant correlation between the eighth grade students’ reading motivation (independent/predictor variable) and reading comprehension achievement (dependent/criterion variable) at SMP Negeri 1 Buay Madang Timur. This research applied correlational study with descriptive method. The population was all of the Eighth grade students of SMP Negeri 1 Buay Madang Timur, with the total number of the students 208 students. The sample was 36 students taken through cluster random sampling method. From the data distribution, it can be said that most of the students tend to have difference score in students’ motivation and reading comprehension tests. The average score of reading motivation and reading comprehension test were 74.14 and 76.81 respectively. The students who have high reading motivation, they also got high reading comprehension achievement. And the students who have enough reading motivation, they also got enough reading comprehension achievement. Based on the findings in this research, it was found that the Pearson correlation coefficient between students’ reading motivation and reading comprehension achievement was 0.80 and exceeds the t-obtained was 7.77. For p>0.05 and df =36-2 =34, the t-table is 2.03224. Because t-obtained was higher than t-table, the correlation coefficient is significant. This means that H0 is rejected and Ha is accepted. Finally, based on the finding of R square in this research it was found that the predictor variable (students’ reading motivation) gave contribution 64% to criterion variable (reading comprehension achievement). The rest 36% were influenced by others factors, like their interest in learning reading, their health or frame of mind on the day they took the test, the frequency of practice, their reading habit, etc.